Pengaruh Kebijakan Hukum Terhadap Perlindungan Hak Asasi Manusia di Negara Berkembang: Studi Pada Negara Berkembang - Ujang Badru Jaman; Yana Priyana; Mursyidin Ar-Rahmany (Westscience Press, 2023)
This research investigates the impact of legal policies on human rights protection in developing countries, focusing on the case of Indonesia. By employing a mixed-method approach, this study combines qualitative and quantitative data to assess the effectiveness of legal measures and their implementation in protecting human rights in Indonesia. The research identifies key human rights challenges, barriers to policy implementation, as well as the roles of civil society and international support in advancing human rights. The findings reveal the positive effects of legal policies and significant challenges in their implementation. Proposed recommendations aim to strengthen human rights protection through legal policies, contributing to a more just and equal society in Indonesia and other developing countries.